2014
DOI: 10.1111/1467-6427.12042
|View full text |Cite
|
Sign up to set email alerts
|

Technology in families and the clinical encounter: results of a cross‐national survey

Abstract: Information communication technologies (ICT) are an integral part of contemporary family life, though the existing research about its impact is scarce, less than definitive, and individually based, as well as failing to attend to cross‐cultural and cross‐national dimensions. This study investigates how family clinicians construe the impact of ICT in the clinical context. A survey directed at family clinicians (N = 258) in four countries (Canada, Mexico, Spain and the USA) was designed to gather data on their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…With TBH also comes many challenges including access to care for the underserved clients who may not have the technological resources, as well as others who do not have the familiarity or capacity to learn this type of new platform as a means to connect. While the use of TBH platforms has been widely established and utilized for over a decade (Bacigalupe, Camara, & Buffardi, 2014; Cabieses, Faba, Espinoza, & Santorelli, 2013), couple and family therapeutic services specifically, and couple and family mental health services in general, have continued to lag in utilization of teletherapeutic services. This problem has been exacerbated by many of the mainstream approaches for working with family systems and subsystems having in focus such transformative foci as the use of space and physical positions (Haley, 1991; Minuchin & Fishman, 1981), the process of physiological and emotional attunement (Greenberg, 2002; Greenberg & Watson, 2006; Shapiro, 2001), and experiential foci for challenging homeostatic problem sequences (Satir et al, 1991; Whitaker & Bumberry, 1988).…”
Section: Covid‐19 and The Structural Changes And Technological Adaptamentioning
confidence: 99%
“…With TBH also comes many challenges including access to care for the underserved clients who may not have the technological resources, as well as others who do not have the familiarity or capacity to learn this type of new platform as a means to connect. While the use of TBH platforms has been widely established and utilized for over a decade (Bacigalupe, Camara, & Buffardi, 2014; Cabieses, Faba, Espinoza, & Santorelli, 2013), couple and family therapeutic services specifically, and couple and family mental health services in general, have continued to lag in utilization of teletherapeutic services. This problem has been exacerbated by many of the mainstream approaches for working with family systems and subsystems having in focus such transformative foci as the use of space and physical positions (Haley, 1991; Minuchin & Fishman, 1981), the process of physiological and emotional attunement (Greenberg, 2002; Greenberg & Watson, 2006; Shapiro, 2001), and experiential foci for challenging homeostatic problem sequences (Satir et al, 1991; Whitaker & Bumberry, 1988).…”
Section: Covid‐19 and The Structural Changes And Technological Adaptamentioning
confidence: 99%
“…Specifically, when working with adolescents with GD, it is important that practitioners are familiar with the nature of GD and the properties of different types of games, such as the fact that some games can be more addictive than the others (King & Delfabbro, 2009). For practitioners to be effective in connecting and working with adolescents with GD, the need for them to first master the complex world of gaming cannot be overemphasized (Bacigalupe et al, 2014;Jordan, 2014).…”
Section: Modeling and Use Of Technologymentioning
confidence: 99%
“…The study has identified the use of technology, specifically by means of Internet games, to be a useful and essential channel to engage adolescents (e.g., King & Delfabbro, 2009;Kuczmierczyk et al, 1987;Park et al, 2014) and to help them reduce the frequency and time of their gaming. The gaming experience, knowledge, and skills of the counselors facilitated the development of therapeutic relationship with adolescents (Bacigalupe et al, 2014). More important, when practitioners are able to master the gaming world, they are able to become models for adolescents in gaming habits.…”
Section: Modeling Trust and Using Technologymentioning
confidence: 99%
“…To understand the eco-systemic context of ICTs in clinicians' personal and professional lives, the current ethos of technology as well as cultural values where professionals live and practice have to be considered. Adding to a previous study with clinicians from Canada, Mexico, Spain and the United States (N = 258; see Bacigalupe et al 2014), this survey (N = 97) was conducted in Turkey. While in the original study family clinicians who used more ICTs themselves saw more benefits for families in general, the Turkish sample, despite using overall more ICTs for non-clinical purposes than their English-and Spanishspeaking counterparts 3 years ago, had a less favorable attitude toward its use in clinical practice.…”
Section: Couple and Family Therapists' Use Of Ictsmentioning
confidence: 99%